1982
DOI: 10.1083/jcb.95.3.974
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activator and collagenase production by cultured capillary endothelial cells

Abstract: Cultured bovine capillary endothelial (BCE) cells produce low levels of collagenolytic activity and significant amounts of the serine protease plasminogen activator (PA). When grown in the presence of nanomolar quantities of the tumor promoter 12-O-tetradecanoyl phorbol-13-acetate (TPA), BCE cells produced 5-15 times more collagenolytic activity and 2-10 times more PA than untreated cells. The enhanced production of these enzymes was dependent on the dose of TPA used, with maximal response at 10 -~ to 10 -8 M.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
143
1
1

Year Published

1986
1986
1998
1998

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 263 publications
(153 citation statements)
references
References 19 publications
8
143
1
1
Order By: Relevance
“…All collagenase was in a latent form and was activated with trypsin to detect activity. The cell layers from these same cultures were washed twice with cold phosphate-buffered saline, pH 7.5, and were extracted with 0.5% Triton X-100 in 0.1 M sodium phosphate, pH 8.1, and the cell extracts were assayed for PA activity as described (15). Previous experiments have demonstrated that the amount of PA in cell extracts is proportional to the amount found in conditioned medium (15).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All collagenase was in a latent form and was activated with trypsin to detect activity. The cell layers from these same cultures were washed twice with cold phosphate-buffered saline, pH 7.5, and were extracted with 0.5% Triton X-100 in 0.1 M sodium phosphate, pH 8.1, and the cell extracts were assayed for PA activity as described (15). Previous experiments have demonstrated that the amount of PA in cell extracts is proportional to the amount found in conditioned medium (15).…”
Section: Methodsmentioning
confidence: 99%
“…Bovine capillary endothelial (BCE) cells were isolated from the adrenal cortex of recently slaughtered yearling cattle by the method of Folkman et al (14). Cells were grown to confluence in a minimal essential medium (aMEM) containing 10% (vol/vol) calf serum and supplemented with medium conditioned by mouse sarcoma 180 cells as described (15). When cultures reached confluence, the medium was changed to aMEM containing 5% (vol/vol) calf serum and no conditioning factors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies have suggested that the ability of specific factors to induce angiogenic responses correlates with their stimulation of matrix protease synthesis in endothelial cells (Gross et al, 1982;Montesano and Orci, 1985). For example, antibodies to interstitial collagenase inhibit endothelial cell invasion (Montesano and Orci, 1985), and metalloprotease inhibitors, such as TIMP, inhibit the angiogenic process (Johnson et al, 1994).…”
Section: Results Bfgf Staining Patterns In Breast Carcinomamentioning
confidence: 99%